A reductive recipe for entrepreneurial team success: Analyzing the individual cognitive strategies and competencies that serve entrepreneurial teams. Issue 1 (13th January 2020) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: This research paper concentrates on the circumstances in which individuals in entrepreneurial teams use effectual and causation-led cognitive strategies. Both of these strategies are employed by teams with high entrepreneurial competence, and in teams with greater entrepreneurial experience the capacity for effectual reasoning is elevated. Such teams are served well by effectual reasoning where the market prospects remain uncertain. Originality/value: The briefing saves busy executives, strategists and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.